Multimode CYTOP fiber interferometric response to laser wavelength scanning - Chapalo, Ivan E.; Petrov, Alexander; Theodosiou, Antreas; Kalli, Kyriacos; Kotov, Oleg I. (My University, 2020)
In this paper, we experimentally investigate the response of CYTOP-based multimode fiber interferometer to variations of the laser’s wavelength. We analyze the interferometric signals of the polymer CYTOP fiber with core diameter of 50 μm for lengths of 1 to 20 meters, using a commercially available FBG interrogator operating for wavelengths from 1510-1590 nm. The analysis was implemented using the averaged characteristics approach. In addition, the results of this work were compared with those of obtained using a silica-based multimode fiber interferometer.
Keywords: CYTOP; Fiber optic sensors; Intermodal interference; Mode-mode interference; Multimode fiber; Perfluorinated fiber; Speckle pattern; Specklegram sensors